KEPUTUSAN PEMBELIAN DITINJAU DARI STORE ATMOSPHERE, VARIAN PRODUK DAN WORD OF MOUTH PADA GENAYAN COFFE BOYOLALI (Studi Kasus Genayan Coffee di Boyolali) - Aisyah Ramadhani (JURNAL ILMIAH EDUNOMIKA, 2022)
This study aims to determine the effect of store atmosphere, product variants and word of mouth simultaneously affect purchasing decisions at Genayan Coffee Boyolali. This type of research includes quantitative descriptive. The population in this study was taken from all visitors at Genayan Coffee Boyolali within a period of 3 months in 2021 and used simple non probability sampling with 100 respondents. Collecting data usingquestionnaire a Likers scale to measure respondents' answers, either positive or negative responses. The analytical technique used for this research is multiple linear regression analysis. The results of this study indicate that there is a significant positive effect of the variable store atmosphere, product variants and word of mouth on coffee purchasing decisions as evidenced by the results of the F test calculated of 115.406> Ftable 2.69 and a significance value of 0.000 from a significance value 3,892 ttable 1.661 and 0.00 significance value of the significant value of 4,705 ttable 1.661 and 0.00 significance value of the significant value of 3,121 ttable 1,661dan significance value of 0.02 of significance value